Status, origin and harvest of increasing numbers of Greylag Geese Anser anser occurring in Denmark throughout the annual cycle - Clausen, Kevin K.; Heldbjerg, Henning; Fox, Anthony D. (Wildfowl, 2023)
Breeding census data and September counts show that numbers of Greylag Geese Anser anser breeding in Denmark have increased more than six-fold in the period 1990–2020. From around the year 2000, the species has also started wintering in Denmark, where mid-winter counts now exceed 100,000 individuals, supporting a substantial increase in the national harvest (> 50,000 Greylag Geese annually since 2014). Rates of increase for all these measures have, however, declined since 2010. To contribute to the sustainable harvest management of such an important migratory quarry species (comprising Danish-breeding geese as well as those originating outside of Denmark), we need to understand both the origin of birds occurring in Denmark during the hunting season and the winter distribution of Danish-breeding birds, yet we lack contemporary information on either. Resighting and recovery data therefore were used to examine the passage and harvest of birds from other countries and to investigate temporal changes in the winter distribution of geese that bred in Denmark. Norwegian-breeding birds passed through Denmark mainly in early autumn, mostly occurring in western Jutland, whereas Swedish-breeding Greylag Geese peaked in numbers during mid-winter and were most numerous in eastern Denmark. In the last two decades, birds from both Norway and Sweden comprised a larger proportion of the Danish hunting bag than before 2000. Late summer reports of birds marked in Germany and Poland likely reflect moult migrants to Denmark during this period. Although marked breeding Greylag Geese from Denmark traditionally overwintered mostly in Spain, recoveries show they have become increasingly sedentary over seven decades, with many now wintering inside Danish national borders. The Northwest/Southwest (NW/SW) European Greylag Goose population (of which Danish birds form a part) is currently the focus of a developing Adaptive Flyway Management Programme, which requires such knowledge of seasonal movements of birds of different origins to ensure informed decision-making and a knowledge-based approach. Our findings can guide decision-making concerning Danish harvest legislation, by quantifying how birds of different breeding provenance contribute to the Danish hunting bag. This may assist with defining the allocation of harvest to comply with attaining the national breeding favourable reference population values established for individual countries.